A Randomized Clinical Trial of an Identity Intervention Programme for Women with Eating Disorders1. (27th September 2012) - Stein, Karen Farchaus; Corte, Colleen; Chen, Ding‐Geng (Din); Nuliyalu, Ushapoorna; Wing, Jeffrey
Abstract Objective Findings of a randomized trial of an identity intervention programme (IIP) designed to build new positive self‐schemas that are separate from other conceptions of the self in memory as the means to promote improved health in women diagnosed with eating disorders are reported. Method After baseline data collection, women with anorexia nervosa or bulimia nervosa were randomly assigned to IIP (n = 34) or supportive psychotherapy (SPI) (n = 35) and followed at 1, 6, and 12 months post‐intervention. Results The IIP and supportive psychotherapy were equally effective in reducing eating disorder symptoms at 1 month post‐intervention, and changes were stable through the 12‐month follow‐up period. The IIP tended to be more effective in fostering development of positive self‐schemas, and the increase was stable over time. Regardless of baseline level, an increase in the number of positive self‐schemas between pre‐intervention and 1‐month post‐intervention predicted a decrease in desire for thinness and an increase in psychological well‐being and functional health over the same period. Discussion A cognitive behavioural intervention that focuses on increasing the number of positive self‐schemas may be central to improving emotional health in women with anorexia nervosa and bulimia nervosa. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.